Law and Legal Consciousness in Medieval Scotland - MacQueen, Hector L., author.
1 online resource (616 pages)
Keywords: This book explores the rise of a Scottish common law from the twelfth century on despite the absence until around 1500 of a secular legal profession. Key stimuli were the activity of church courts and canon lawyers in Scotland, coupled with the example provided by neighbouring England’s common law. The laity’s legal consciousness arose from exposure to law by way of constant participation in legal processes in court and daily transactions. This experience enabled some to become judges, pleaders in court and transactional lawyers and lay the foundations for an emergent professional group by the end of the medieval period.